Recipient synchronization with various prostaglandin f2α protocols for embryo transfer in cows - Mesut Kırbaş; Şükrü Dursun; Mehmet Köse; Bülent Bülbül; Mehmet Çolak; Hasan Mutlu (Eurasian Journal of Veterinary Sciences)
Aim: In this study, recipient synchronization with various prostaglandin F2α protocols for cryopreserved embryo transfer was examined. Materials and Methods: A total of 46 Brown Swiss cows assigned randomly into three groups. Group I (n=15) cows injected 0.150 mg cloprostenol intramuscularly at random stage of the oestrus cycle. Following the injections, cows were observed for oestrus for 5 days. The other cows were received two 0.150 mg I.M. injections of cloprostenol 11 (Group II, n=15) or 14 (Group III, n=16) days apart. In Group II and III, cows were observed for oestrus for 5 days after the last injections. All cows were transferred embryos cryopreserved by ethylene glycol on d 7 (oestrus 0). Pregnancy diagnoses were performed on d 28 by ultrasonography. Results: Injection-oestrus intervals and pregnancy rates were 56.13±4.37 h and 53.3%; 62.40±3.42 h and 46.7%; 70.75±3.08 h and 43.8% in groups I, II and III, respectively. Injection-oestrus interval was lower in Group I than in Group III (p<0.05) and was similar between groups I and II and groups II and III (p>0.05). The differences in pregnancy rates among groups were not significant (p>0.05). Conclusions: All synchronization protocols evaluated in this study can be used for oestrus synchronization for cryopreserved embryo transfer in cows.